Mainstreaming Civic Engagement into Water Supply Management in Kondoa District Council, Tanzania - Benedict Anselm, Sulley (Journal of Public Administration and Governance, 2022)
One of the significant changes made by the Government of Tanzania over the last two decades is mainstreaming of civic engagement mechanisms into water supply management. This instigation is motivated by the belief that civic engagement would contribute to greater voice and oversight of government functions through shared decisions, responsibility, transparency, trust and respect of public input. However, little evidence affirms the capability of citizens to articulate their voice in water service decision-making spaces. It is obvious that citizens’ ability to articulate their voice is associated with the extent to which their voices are mainstreamed in water service decision-making spaces. This study, therefore, examined the extent to which citizens’ voices are mainstreamed in water service decision-makings spaces. A mixed-method approach was used to generate data through survey of 376 households, 4 focus group discussions, 14 in-depth interviews, and field observations. The result shows that the spaces for decision making are moderately open for citizens but they are less capable to influence the pre-determined position of the public officials. There is also a lack of citizens’ readiness to engage with government to some provided responsibilities in National Water Policy of 2002 and National Water Resources Management Act of 2009. All these hold-ups are a result of unclear ownership of water infrastructure and, therefore, citizens assumed it the responsibility of the government alone to deliver and maintain water sources. The author recommended for citizen’s empowerment for creating awareness and capacity interventions for effective water supply management.